Affective responses to sweet products and sweet solution in British and Finnish adults. (December 2017) - Tuorila, Hely; Keskitalo-Vuokko, Kaisu; Perola, Markus; Spector, Tim; Kaprio, Jaakko
Highlights: Responses to sweetness collected from Brits (17–82 years) and Finns (20–25 years). Liking for sucrose solution (20%) and 10 sweet products (by name) evaluated. British men at higher age (>50 years) tended to like sweetness best. Finnish women liked and craved sweetness more than Finnish men. Liking for solution was a poor predictor of liking (based on name) for sweet products. Abstract: Responses to sweetness are reported in two populations, one segmented by gender and age, and the other one by gender only. The strength of the association between liking for specific sweet foods and liking for an aqueous sucrose solution (20% w/v) is also tested, and health attitudes examined. British adults (n = 1855, age 17–82, mean 55 years, 90% women) and Finnish young adults (n = 1292, age 20–25, mean 22 years, 54% women) rated their liking of ten sweet foods and beverages based on product names, and completed questionnaires on Craving for Sweet Foods (CSF) and General Health Interest (GHI). One-half of Brits and a third of Finns rated liking and intensity of sucrose solution. In factor analysis, identical categories of liking for sweet products were formed in each population, one consisting of five processed sweets ("Goodies"), and the other of naturally sweet fruits and berries ("Fruits"). Sugared and sugar-free s oft drinks and fruit juice loaded on the third factor. After age 50, British men scored higher than British women in CSF and liking for several sweet products; Finnish women scored higher than Finnish men in CSF and liking for most sweet products. GHI was positively associated with liking for Fruits and negatively with liking for sugared soft drinks. Sucrose solution was better liked by British men than women, with no gender difference in Finns. Liking for sucrose solution was only weakly associated with liking for sweet products based on product names. In two demographically different European populations, attraction to sweet gathered in similar product categories, but manifested differently at different ages and each gender.